Improving Business Process In Constructing Rencana Strategi Diskoperindag Using Business Process Improvement (bpi) Method(fulfilling The Requirements Of Minister Of Home Affair Regulation Number 54 Of 2010 And Iso 9001:2008 Clause 7.3) - Romyah Bighoiri Romy; Sri Widaningrum; Atya Nur Aisha (eProceedings of Engineering, 2015)
Abstract DISKOPERINDAG of Bandung Regency has a role in preparing the development planning documents; one of them is Renstra (Rencana Strategi). In existing condition, DISKOPERINDAG Renstra has compatibility issue with The Minister of Home Affair Regulation Number 54 of 2010. This research is aimed to improve the business process of constructing Renstra DISKOPERINDAG based on The Minister of Home Affair Regulation Number 54 of 2010 and the ISO 9001:2008 Clause 7.3, to ensure the Renstra to be able to meet customer’s expectation. This research was using BPI method to improve the business process of constructing Renstra. The improvement was started by performing activity analysis. The result of activity analysis shows that there are 14 RVA activities, 13 BVA activities and 0 NVA. Streamlining was performed to increase efficiency of the process. RACI matrix was used to determine the process owner of each activities. There are 5 activities in existing business process and 22 activities in the proposed business process. The proposed business process was trafered onto the SOP to facilitate a consistent conformance and to ensure a well-documented process. The result of this research is 1 SOP of Renstra Construction and 7 work instructions to support the SOP. Keyword: Renstra, ISO, BPI, RACI, SOP